Effects of postexercise cooling on heart rate recovery in normotensive and hypertensive men. (19th December 2019) - Peçanha, Tiago; Low, David; de Brito, Leandro Campos; Fecchio, Rafael Yokoyama; de Sousa, Patrícia Nascimento; da Silva‐Júnior, Natan Daniel; de Abreu, Andrea Pio; da Silva, Giovanio Vieira; Mion‐Junior, Décio; Forjaz, Cláudia Lúcia de Moraes
Summary: Background: Postexercise heart rate recovery (HRR) is determined by cardiac autonomic restoration after exercise and is reduced in hypertension. Postexercise cooling accelerates HRR in healthy subjects, but its effects in a population with cardiac autonomic dysfunction, such as hypertensives (HT), may be blunted. This study assessed and compared the effects of postexercise cooling on HRR and cardiac autonomic regulation in HT and normotensive (NT) subjects. Methods: Twenty‐three never‐treated HT (43 ± 8 years) and 25 NT (45 ± 8 years) men randomly underwent two exercise sessions (30 min of cycling at 70% VO2peak ) followed by 15 min of recovery. In one randomly allocated session, a fan was turned on in front of the subject during the recovery (cooling), while in the other session, no cooling was performed (control). HRR was assessed by heart rate reductions after 60 s (HRR60s) and 300 s (HRR300s) of recovery, short‐term time constant of HRR (T30) and the time constant of the HRR after exponential fitting (HRRτ). HRV was assessed using time‐ and frequency‐domain indices. Results: HRR and HRV responses in the cooling and control sessions were similar between the HT and NT. Thus, in both groups, postexercise cooling equally accelerated HRR (HRR300s = 39±12 versus 36 ± 10 bpm, P ≤0·05) and increased postexercise HRV (lnRMSSD = 1·8 ± 0·7 versus 1·6 ± 0·7 ms, P ≤0·05). Conclusion: Differently from the hypothesis, postexercise cooling produced similar improvements in HRR in HT and NT men, likely by an acceleration of cardiac parasympathetic reactivation and sympathetic withdrawal. These results suggest that postexercise cooling equally accelerates HRR in hypertensive and normotensive subjects.